Technology Adaptation as a Driver of Process Innovation: Evidence From Culinary MSMEs in West Java, Indonesia - Rena Yuliana; Reka Ramadhan (Sanskara Manajemen Dan Bisnis, 2026)
Technology adaptation has become an important driver of process innovation among micro, small, and medium-sized enterprises (MSMEs) in the digital era. However, empirical evidence regarding this relationship remains limited, particularly in the context of culinary MSMEs in developing countries. This study examines the effect of technology adaptation on process innovation among culinary MSMEs in West Java Province, Indonesia. A quantitative explanatory approach was employed using survey data from 376 culinary MSMEs selected through purposive sampling. Data were analyzed using Weighted Least Squares (WLS) regression after correcting for heteroscedasticity in the initial regression model. The results indicate that technology adaptation has a positive and significant effect on process innovation (β = 0.615; t = 15.077; p < 0.001). The findings suggest that MSMEs with stronger capabilities to integrate digital technologies into their operational activities are more likely to improve business processes through greater efficiency and responsiveness. This study reinforces the Technology–Organization–Environment (TOE) Framework by demonstrating that organizational capability to adapt technology is a key determinant of process innovation. The findings also provide practical insights for policymakers and business development agencies in designing digital capability development programs to enhance innovation among MSMEs.